Design of indoor model test system for Post-stiffened core lengthened concrete pile. Issue 7 (April 2020) - Li, Yue-Ming; Han, Shang-Yu; Li, Kai-Ren
Abstract: The post-stiffened core lengthened concrete pile is a kind of composite foundation pile formed after the existing concrete core is inserted into the stiffened core lengthened body through the hole. Based on the pile-forming technology and testing needs of the pile structure, a set of indoor model test system is studied and determined. The system is mainly composed of model groove, loading system and measuring system, and the setting of post-stiffening core section can be realized by controlling the filling time of concrete in the existing concrete core position. The displacement test body is set up on the top of the model pile and the soil around the pile, the stress sensor is set in the pile body and the core body, and the earth pressure sensor is set in the soil around the pile. The test system can form the bearing capacity of pile body (including existing concrete pile and stiffening core section) and soil around the pile from multiple dimensions, and realize the test of pile response under different load combinations by controlling the loading process.